Risk of road traffic accidents in children - Goniewicz, Krzysztof; Goniewicz, Mariusz; Pawłowski, Witold; Fiedor, Piotr; Lasota, Dorota (Medical Studies/Studia Medyczne, 2017)
Injuries resulting from road accidents are the most common cause of death among children, more common even than cancer and birth defects. There were 135,438 accidents involving children aged 0–14 years in the years 2000–2014 in Poland. A total of 4334 children died and 141,009 were injured. Most fatalities were recorded among children between the ages of 7 and 14 years. The research presents the main problems of road safety and the nature of the causes and consequences of accidents among children in Poland. Injuries to children are one of the biggest problems in modern medicine, which requires vigorous and preventive actions. Children of all ages should be intensively covered by educational activities related to road safety. Raising awareness of the risks associated with participation of children in traffic, with parents and carers, can greatly reduce the number of accidents.